Association between gene polymorphisms in the cyclophosphamide metabolism pathway with complications after haploidentical hematopoietic stem cell transplantation - Muñiz, Paula; Andrés-Zayas, Cristina; Carbonell, Diego; Chicano, María; Bailén, Rebeca; Oarbeascoa, Gillen; Suárez-González, Julia; Gómez Centurión, Ignacio; Dorado, Nieves; Gallardo, David; Anguita, Javier; Kwon, Mi; et al. (Frontiers in Immunology, 2022)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a curative treatment for patients with hematologic malignances. Haploidentical HSCT (Haplo-HSCT) is an alternative option for patients who do not have an HLA-matched donor. The use of post- transplantation high dose cyclophosphamide (PT-Cy) is commonly employed for GVHD prophylaxis in haplo-HSCT. Cyclophosphamide (Cy) is an alkylating agent with antineoplastic and immunosuppressive activity, whose bioactivation requires the activity of polymorphic enzymes in the liver to produce phosphoramide mustard, which is a DNA alkylating agent. To identify polymorphisms in the genes of Cy metabolism and correlate them with post-HSCT complications (graft-versus-host disease (GVHD), sinusoidal obstruction syndrome (SOS), hemorrhagic cystitis (HC) and transplant-related mortality (TRM)), we designed a custom next-generation sequencing panel with cyclophosphamide metabolism enzymes. We analyzed 182 patients treated with haplo-HSCT with PT-Cy from 2007 to 2019, detecting 40 variants in 11 cyclophosphamide metabolism genes. Polymorphisms in CYP2B6, a major enzyme involved in cyclophosphamide activation, were associated with decreased activity of this enzyme and a higher risk of GVHD. Variants in other activation enzymes (CYP2A6, CYP2C8, CYP2C9, CYP2C19) lead to decreased enzyme activity and were associated with GVHD. Polymorphisms in detoxification genes such as glutathione S-transferases decreased the ability to detoxify cyclophosphamide metabolites due to lower enzyme activity, which leads to increased amounts of toxic metabolites and the development of III-IV acute GVHD. GSMT1*0 a single nucleotide polymorphism previously recognized as a risk factor for SOS was associated with a higher risk of SOS. We conclude that polymorphisms of genes involved in the metabolism of cyclophosphamide in our series are associated with severe grades of GVHD and toxicities (SOS and TRM) after haplo-HSCT and could be used to improve the clinical management of transplanted patients.